Topical glucocorticoid reduces the topical decongestant-induced histologic changes in an animal model nasal mucosa - AKAKIN, DİLEK; ÖZKAN YENAL, NAZİYE; ŞEHİRLİ, ÜMİT SÜLEYMAN (WILEY, 2012)
Objectives/Hypothesis: To investigate the histologic consequences of simultaneous nasal glucocorticosteroid and xylometazoline HCl administration in the rabbit nasal mucosa. Study Design: Prospective randomized study. Methods: Twenty New Zealand male rabbits were randomly placed into three groups: group I, control (n 6); group II, xylometazoline HCl (n 8); or group III, xylometazoline HCl- fluticasone furoate (n 6). Group I received no treatment. Groups II and III received two intranasal puffs of xylometazoline HCl 0.5 mg/ mL twice daily or two puffs of xylometazoline HCl 0.5 mg/ mL twice daily plus one puff of 27.5 lg fluticasone furoate twice daily to each nostril (110 lg), respectively. At the end of 3 weeks, the rabbits were sacrificed. The mucosa of the nasal cavities was excised. Specimen sections (5 lm) were stained with hematoxylin and eosin, mucicarmine, and Gomori one- step trichrome and were examined under a light microscope. The presence of edema, congestion, inflammatory cell infiltration, nasociliary loss, epithelial and nerve- ending degeneration, and goblet cell increase were evaluated semiquantitatively (grades 0- 3). Results: Statistically significant differences were detected between groups II and III in terms of edema, congestion, inflammatory cell infiltration, nasociliary loss, and epithelial degeneration (P.006, P.049, P.015, P.014, and P.049, respectively). Nerve- ending degeneration, goblet cell increase, and quantitative goblet and neutrophil cell counts did not yield statistically significant differences between groups II and III (P.137, P.580, P.770, and P.616, respectively). Conclusions: The combined simultaneous intranasal administration of xylometazoline HCl and fluticasone furoate appears to be beneficial in minimizing the long- term usage- associated congestion, edema, inflammatory cell infiltration, epithelial degeneration, and nasociliary loss in the rabbit model nasal mucosa.
Keywords: Nasal mucosa; rhinitis medicamentosa; congestion; decongestant; nasal steroid; rebound; edema; Level of Evidence: 2c; RHINITIS-MEDICAMENTOSA; BENZALKONIUM CHLORIDE; REBOUND CONGESTION; ALLERGIC RHINITIS; OXYMETAZOLINE; SPRAY; TACHYPHYLAXIS; MECHANISM; SYMPTOMS; EFFICACY